TRANSFORMASI PENDIDIKAN AGAMA ISLAM PADA PONDOK MODEREN BOARDING SCHOOL MTSN 1 KOTA BIMA - Mariani, Mariani; Samsudin, Samsudin (JEMARI : Jurnal Edukasi Mahasiswa Sunan Giri, 2023)
This research aims to find out what the Islamic religious education learning system is like at MTsN 1 Bima City before and after the existence of the Boarding School. The method used in this research is a qualitative method. Collect data using observation, interview and documentation techniques. The research results show that the Boarding School was introduced because the school wanted its students to memorize the Al-Qur'an, as well as special training in several other fields. And this Boarding School has been running for 12 years, from this coaching students reap extraordinary results.